Pemanfaatan Laptop Gadget dan Printer (Laga Pinter) Sebagai Media Pembelajaran Pada Materi Segi Empat Siswa Kelas VII K SMP Negeri 5 Kendari - Asri Azis (Jurnal Didaktika Pendidikan Dasar, 2021)
Laga Printer is a learning media which covers laptop, gadget, and printer as a solution for students’ learning difficulties in working on mathematic problems on types and characteristics of rectangular.  The aim of using Laga Printer is to improve students’ learning efficacyat class VII K SMP Negeri 5 Kendari on types and characteristics of rectangular. The use of Laga Printer in the learning process was designed in the form of classroom action research method which was carried out in two meetings. Instruments of this study covers achievement test and questionnaires. This study showed that from 30 students assigned to the test,26 students (86.66%) achieved mastery learning with scores ≥ 73. On skill aspect, 19 students (63.33%) had very good category and 7 students (23.33%) had good category. Students’ questionnaires analysis pointed out that 25 students (83.33%) were very satisfied and 3 students (10.00%) were satisfied with Laga Printer. The practical value of 78 showed that Laga Printer is a practical learning media. Thus, this study concludes that the use of Laga Printer as a learning media can make students learn better and improve their learning efficacyat class VII K SMP Negeri 5 Kendari.